EDUCATION AND ALIENATION IN RELATION TO IMMEDIACY AND ACADEMIC PRODUCTIVISM: A POSSIBLE DIALOGUE (Editora Impacto Científico, 2025)
The following article presents an analysis of the relationship between education and alienation, and academic productivism as work carried out by people who, although responsible for this work, are separated from it. Two aspects were considered to establish this parallel: firstly, because the act of writing scientific texts constitutes a labor activity; in this sense, the worker is undertaking effort, similar to the labor force exerted in industry, with due regard to specificities. Secondly, because these people may be alienated from the product of their work. But we also consider that, just as the alienated worker did not recognize themselves in what they did, the work was foreign to them, productions devoid of critical sense follow the speed inherent in an industrial production line, serving the mode of production inherent in the capitalist system, and for this reason, it becomes work devoid of critical sense. Supporting this analysis is the reflection on theme II of the UESB 2013 entrance exam essay, titled "Reason in a Coma," which dealt with the loss of values ​​and culture, aiming to produce a critical essay focusing on the relationship between "immediacy, the lack of reflection in contemporary society, and its consequent devaluation of culture." Thus, we infer that immediacy has already been the subject of attention in academia. The method used to capture the phenomenon was Marx's historical materialism, and specifically a fundamental category of this method: alienation of labor, a concept found in the Grundrisse (outlines) and in the work, The German Ideology. The text also presents Saviani's concept of marginality, in the sense of considering who is marginalized in higher education today. Finally, the text presents the concept of intellectual, considering the social role of the intellectual as one who engages with the demands inherent to our time.DOI: https://doi.org/10.56238/edimpacto2025.090-037